10 Years of the Palliative Medicine Working Group in the Network of Top Oncology Centers - Berendt, Julia; Gahr, Susanne; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-01-14

Acute confusional states and delirium in palliative care - Jentschke, Elisabeth; Roch, Carmen; Reinholz, Ulrike; Gahr, Susanne; Gaertner, Jan; Lewerenz, Jan; Mayer-Steinacker, Regine; Oechsle, Karin; Villalobos, Matthias (Die Onkologie, 2023)
CRIS-Team WoS Importer:2023-03-03

Are There Entity-Specific Criteria for Initiation of Specialized Palliative Care for Incurable Cancer? A Scoping Review - Gahr, Susanne; Brunner, Sarah; Heckel, Maria; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2023)
Background/Objective Finding the right time for offering specialized palliative care to patients with incurable cancer remains challenging. The aim of the scoping review was to identify appropriate entity-specific criteria. Method A scoping review was conducted in the online databases PubMed and Scopus in February 2020. The aim of the literature search was to identify original English- and German-language papers published between 2009 and February 2020 providing evidence on which entity-specific and entity-independent criteria of non- curable cancers are used to integrate affected patients into specialized palliative care in a timely manner. A total of 13 relevant articles were identified. In accordance with the method of the scoping review, a formal assessment of the methodological quality of the included literature was not performed. Results The relevant publications included six reviews and seven original articles. None of the publications analysed explicitly cited characteristic criteria related to specific cancer entities. Incurability/advanced tumour disease, quality of life, distressing symptoms, ECOG status, psychosocial needs, comorbidities, tumour-associated complications, treatment decision/ no treatment options, and limited lifetime prognosis were used or suggested as criteria for integration into specialized palliative care independently of cancer entity. Tools were used to elicit the criteria. No specific characteristic scores were specified for the tools that could detect an expression of the criteria relevant for integration into specialized palliative care. Conclusion To determine the moment of timely integration of specialized palliative care for non-curable cancers, there are no entity-specific criteria and parameters to date. However, it can be deduced from the analysis that all patients with a non-curable or advanced cancer suffering from a reduction/loss of their quality of life and a complex symptom burden, especially depression and pain, should receive the offer of specialized palliative care, irrespective of their entity. Defining criteria in general as characteristic values and consecutively defining a measured value or cutoff value could be a possibility to facilitate a timely integration of palliative care via e. g., a scoring system. So far, it is unclear which combinations of survey instruments or screening tools could serve to capture timely integration.
CRIS-Team WoS Importer:2023-05-05

Health- and disease-related data of inpatients in palliative care units of the Comprehensive Cancer Centers and other hospitals in comparison-Data from the Hospice and Palliative Care Register - Brunner, Sarah; Heckel, Maria; Zenz, Daniel; Ostgathe, Christoph; Gahr, Susanne (Wiener Medizinische Wochenschrift, 2022)
Background The National Hospice and Palliative Registry is a database for palliative care facilities documenting a core data set for quality assurance and scientific evaluations. Objectives The study aims identifying differences between patients in palliative care units treated in Comprehensive Cancer Centers (CCC) or other hospitals (OH) focussing on sociodemographic and health/disease-related characteristics. Methods Descriptive data analysis using IBM SPSS Statistics 21 included patients treated from 2014 to 2018. Comparisons included sociodemographic data, diagnoses, ECOG status and treatment duration. Results 12,922 patient data were analyzed (CCC n = 4975/OH = 7947). In CCCs 79.8% had a tumor diagnosis, in other hospitals 85.1%. The proportion of patients with ECOG 4 was higher in CCCs than in other hospitals. The average length of stay in CCCs was 12.6 days, in other hospitals 11.3 days (p = 0.023). Conclusions Data show differences between patients in palliative care implicating CCCs treating more complex palliative care patients than other hospitals.
CRIS-Team WoS Importer:2022-02-11

Implementation of Best Practice Recommendations for Palliative Care in German Comprehensive Cancer Centers - Gahr, Susanne; Lödel, Sarah; Berenot, Julia; Thomas, Michael; Ostgathe, Christoph (Oncologist, 2019)
Background From 2014 to 2017, the Palliative Medicine Working Group developed and published best practice recommendations for the integration of palliative care in Comprehensive Cancer Centers (CCCs) in Germany. To evaluate the implementation level of these recommendations in the CCCs an online survey was performed. Based on the results of this study, strategic tandem partnerships between CCCs should be built in order to foster further local development. Materials and Methods Directors of all CCCs were contacted by e-mail between December 2017 and February 2018. At the time of the survey, 15 CCCs were funded by the German Cancer Aid. The level of implementation of the recommendations in individual CCCs was established using a transtheoretical model. Results Between December 2017 and February 2018, all 15 contacted directors or their representatives of the CCCs took part in the survey. More than two thirds of the CCCs have a palliative service as well as a day clinic and palliative outpatient clinic. Regional networking and the provision of a palliative care unit were approved by all CCCs. Conclusion The publication of best practice recommendations was a milestone for the integration of palliative care in the CCCs. The majority of the German CCCs already fulfill essential organizational and structural requirements. There is a particular need for optimization in the provision of a basic qualification for general palliative care and emergency admission personnel. Implications for Practice In 2017, the Palliative Medicine Working Group in the network of the German Comprehensive Cancer Centers (CCCs) published the best practice recommendations it had developed for the integration of palliative medicine in CCCs in Germany. In order to evaluate the level of implementation of the recommendations, an online survey of the CCC directors was established. The majority of German CCCs fulfil elementary organizational and structural requirements. However, there is still room for improvement in the provision of a basic qualification for general palliative care and emergency admission personnel.
CRIS-Team WoS Importer:2019-09-27

Palliative Care Teams in the German Comprehensive Cancer Centers - Gahr, Susanne; Berendt, Julia; Lödel, Sarah; Ostgathe, Christoph; Simon, Steffen T.; Tewes, Mitra; Zader, Kirsten; Schwartz, Jacqueline; Neukirchen, Martin (Deutsche Medizinische Wochenschrift, 2019)
BACKGROUND: A palliative care team is recognized as a quality indicator in the consultation and care of patients with a tumor disease and is used nationally (92 %) in the National Cancer Institutes, model of the German Comprehensive Cancer Center (CCC). This begs the question of how palliative care teams are presently integrated into the CCCs. METHOD: From July to August 2017, a paper-based quantitative survey of 16 locations of the CCCs, supported to that date, gathered information on the existence, personnel situation, use and prospects of a specialized inpatient palliative care service. The survey was addressed to the heads of the palliative medical units of the CCCs. The data were evaluated in SPSS (frequency, median, mean, range). RESULTS: Fifteen CCCs took part in the survey (response 94 %). Thirteen of the fifteen CCCs have a service that also treats palliative patients. Twelve of thirteen CCCs of these are attainable during regular working hours (8a. m.-4 p. m. on weekdays). All services are staffed by physicians, additional eleven are staffed by nurses. Seven services are besides physicians and nurses joined by other professions. In 2016, 4482 median co-treatments were provided by the services, 80 % of these as additional charges without revenue and without codable OPS. In 2017, five centers plan to charge ZE 2017-133, two centers ZE 60 and three centers both intend to charge ZE 2017-133. CONCLUSIONS: Services for palliative patients exist generally in the German CCCs, but only half of them satisfy the condition of multi-professionality required for the fulfillment of the german guidelines. The new surcharge introduced in 2017, which can be charged on an hourly basis, could create improvements in this regard and contribute to cost recovery. Thus, contrary to the previous arrangement, essential and reasonable performances with a time of treatment of less than seven days can be charged.
EVALuna2:204833

Palliativmedizin in onkologischen Spitzenzentren - Gahr, Susanne; Berendt, Julia; Tewes, Mitra (Forum, 2023)
Die bestmögliche Versorgung schwerstkranker und sterbender Patienten vom Zeitpunkt der Diagnosestellung bis zum Tod ist eine zentrale Aufgabe der Palliativversorgung onkologischer Zentren und Spitzenzentren. Die dynamische Entwicklung der Palliativmedizin in den letzten Jahren hat dabei zu einer sehr heterogenen Versorgungslandschaft mit unterschiedlichen Angeboten und Konzepten geführt. Vertreter der Arbeitsgruppe Palliativmedizin aus den durch die Deutsche Krebshilfe geförderten Comprehensive Cancer Centers (CCCs) haben für viele Bereiche der Patientenversorgung, Forschung und Lehre die Notwendigkeit erkannt, die Integration der Palliativmedizin in die etablierten Strukturen und klinischen Abläufe mit ihren gebündelten Kompetenzen zu intensivieren, innerhalb und außerhalb der CCCs. Aufgaben und Ziele der Arbeitsgruppe Palliativmedizin bestehen in der gemeinsamen Vernetzung, im fachlichen Austausch und in der Entwicklung gemeinsamer Standards sowie darin, die Erkenntnisse anderen onkologisch versorgenden Einrichtungen zur Verfügung zu stelle
Keywords: Onkologie; Palliativversorgung; Comprehensive Cancer Centers; Vernetzung; Behandlungsstandards

Palliativmedizin: von zeitgerechter Integration bis Umgang mit unerträglichem Leid - Gahr, Susanne; Ostgathe, Christoph; Steigleder, Tobias (Frauenheilkunde up2date, 2024)
Palliativmedizin ist laut WHO die aktive, ganzheitliche Behandlung von Patienten mit einer lebensbedrohlichen Erkrankung und deren Angehörigen, um bestmögliche Lebensqualität zu erreichen [1]. Die Linderung von Schmerzen und anderen Beschwerden – körperlicher, psychischer, sozialer und spiritueller Art – haben dabei höchste Priorität. Dieser Beitrag zeigt, wie Palliativpatienten in unterschiedlichen Phasen der Erkrankung unterstützt werden könne
Keywords: Palliativmedizin; Screening; zeitgerechte Integration; palliativmedizinischer Dienst; gezielte Sedierung

Palliativversorgung im finalen Tumorstadium: Sinnvolle Strategien für die Versorgung im Delir - Gaertner, Jan; Gahr, Susanne; Reinholz, Ulrike; Kunz, Roland; Jentschke, Elisabeth; Roch, Carmen (Deutsches Ärzteblatt, 2022)
Patientinnen und Patienten in fortgeschrittenen und vor allem in finalen Tumorstadien entwickeln häufig delirante Zustände. Neben der Prävention und Beseitigung von möglichen Ursachen steht oft auch die Frage einer medikamentösen Sofortintervention im Rau

Scoping Reviews in Palliative Research - Heckel, Maria; Berendt, Julia; Gahr, Susanne; Kauzner, Saskia; Schleef, Tanja; Herbst, Franziska A. (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-12-16

Screening for specialist palliative care need: Know-how and screening tools Screening auf Bedarf an spezialisierter Palliativversorgung: Know-how und Screeningtools - Müller, Evelyn; Gahr, Susanne; Schnabel, Astrid; Müller, Michael Josef; Sölder, Paul; Tewes, Mitra; Roch, Carmen (Die Onkologie, 2024)
Aim: Specialist palliative care (SPC) should be integrated into the care of patients with advanced cancer with complex symptoms and high burdens. The aim of this publication is to present the screening tools that have the highest relevance for the identification of patients in need of SPC in Germany and that are the most feasible in practice; concrete advice for implementation in practice is also given. Methods: This publication summarizes the results of the subworking group “Screening and timely integration” of the working group Palliativmedizin (CCC Network). These are based on a systematic literature search in Medline and CINAHL that aimed to identify screening tools for SPC need in oncology. Results: From the range of possible screening approaches, the use of patient questionnaires, which are recommended in the German standard operating procedure (SOP) Basic Oncological Screening and are also suitable for SPC screening, is particularly effective. The most relevant options for Germany are the Integrated Palliative Care Outcome Scale (IPOS) and the NCCN Distress Thermometer and Minimal Documentation System (MIDOS2). Initial studies show that these questionnaires have the potential to identify 78–90% of patients in need of SPC using validated cut-off values. Conclusion: Patients with a positive screening result for SPC need are highly burdened. The extent to which the needs can be addressed by the oncological teams or whether SPC should be integrated must then be evaluated. Both patient preferences and local resources of general and specialist palliative care should be taken into account.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Palliative care needs/Patient questionnaires; Palliative care needs/Third party assessment; Patient-reported outcome measures; Screening/Implementation; Tumor diseases/Neoplasms

SOP - Management of multiresistent Pathogens in the Palliative Care Unit - Ostgathe, Christoph; Stachura, Peter; Heckel, Maria; Brunner, Sarah; Gahr, Susanne; Hofmann, Sonja; Van Oorschot, Birgitt; Oechsle, Karin; Bogdan, Christian; Kunz, Bernd; Foertsch, Baerbel; Klein, Carsten (Die Onkologie, 2022)
Infobox 1 SOP aus der Reihe „SOPs zur palliativen Versorgung von Patienten im Netzwerk der deutschen Comprehensive Cancer Center“, erstellt von der AG Palliativmedizin der von der Deutschen Krebshilfe geförderten Comprehensive Cancer Center (CCC
CRIS-Team WoS Importer:2022-10-07

Standard Operating Procedures (SOPs) for Palliative Care in German Comprehensive Cancer Centers - An evaluation of the implementation status - Lödel, Sarah; Ostgathe, Christoph; Heckel, Maria; Oechsle, Karin; Gahr, Susanne (BMC Palliative Care, 2020)
Background: The working group for palliative medicine within the Comprehensive Cancer Center (CCC) network funded by the German Cancer Aid in Germany has developed and published 14 Standard Operating Procedures (SOPs) for palliative care in CCCs. This study analyzed to what extent these SOPs have been implemented in the clinical routine in the CCC network one year after their publication. Methods: An online-based survey on the implementation status, limitations in daily practice and further themes was conducted between April and July 2018. In total, 125 health professionals in specialized palliative care from all 16 CCC locations were invited to participate. The data were analyzed descriptively using SPSS. Results: The response rate was 52.8%. More than half of the respondents (57.6%) knew about the free availability of SOPs on the CCC network website. The extent to which each SOP was being used actively in practice by the survey respondents ranged from a low of 22.7% (for the "Fatigue" SOP) to a highest of 48.5% (for the "Palliative Sedation" and "Respiratory Distress" SOPs). The respondents became aware of the SOP through recommendations from colleagues, team meetings or from the head of the department. The SOPs "Respiratory distress of an adult palliative patient" and "Palliative sedation" were perceived as the most practically oriented and understandable. Barriers to use SOPs were mainly limited time resources and lack of knowledge of existence and availability. Conclusions: In practice, better knowledge about the SOPs and at the same time increased use can be achieved through systematic training or discussion of SOPs in regular team meetings. There is a need to take measures to optimize the implementation in clinical practice.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Comprehensive Cancer Center (CCC); Implementation status; Palliative Care; Standard Operating Procedure (SOP); Survey; Symptoms

Symptom burden and relief in palliative care units of German Comprehensive Cancer Center and other hospitals - Berendt, Julia; Brunner, Sarah; Heckel, Maria; Tewes, Mitra; Ostgathe, Christoph; Gahr, Susanne (Journal of Cancer Research and Clinical Oncology, 2024)
Purpose: The National Hospice and Palliative Registry contains patient data from German hospice and palliative care facilities about symptoms. The aim of the study at hand is to differentiate symptom burden of patients in palliative care units between Comprehensive Cancer Center (CCC) and other hospitals regarding symptom burden and relief of patients in palliative care units. Methods: The registry analysis provided data of patients in palliative care units (2014–2018). We analyzed characteristic and symptom-related data on 18 symptoms, with considerable symptom-burdened patients (moderate or severe). We followed a cancer (yes/no) and facility-specific descriptive analysis (f, %, μ, Mdn, SD, V, r) using SPSS. Results: We evaluated 10,447 patient records (CCC: 4234 pts/non CCC 6,213 pts), 82% with a cancer diagnosis. For cancer patients, the mean age in CCC-affiliated palliative care units was 68 (SD 19–99) years, in others 73 (SD 23–104) years (p < 0.05; V = 0.2). The proportion of patients with significant symptom burden is lower in CCC-affiliated than in other palliative care units. The difference between facilities shows a significant weak effect in pain, vomiting and constipation, depressiveness, anxiety, and tension. The proportion of cases which symptom burden could be alleviated is higher in CCC-affiliated palliative care units with significant weak/medium effect in pain, nausea, vomiting, shortness of breath, constipation, wound care problems, depressiveness, anxiety, tension, confusion, and problems in organizing care. Conclusion: We found differences in symptom burden and symptom relief between CCC-affiliated and other palliative care units. CCCs should continue to feel responsible for sharing knowledge about symptom relief, such as through standard operating procedures and education.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Cancer; Palliative care; Registry; Symptom burden; Symptom relief

Zusammenarbeit von Intensivmedizin und Palliativmedizin: Eine Bestandsaufnahme an den deutschen onkologischen Spitzenzentren - Berendt, Julia; Ostgathe, Christoph; Simon, S. T.; Tewes, M.; Schlieper, D.; Schallenburger, M.; Meier, S.; Gahr, Susanne; Schwartz, J.; Neukirchen, M. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Background: For intensive care patients with limited life expectancy the integration of palliative care in intensive care may be beneficial. However, little is known about the extent of this interdisciplinary collaboration. Objectives: The support given by palliative medicine in German oncological centers and used by the intensive care units should be recorded. Material and methods: A descriptive survey was conducted in all of the 16 Comprehensive Cancer Centers (CCC) funded by German Cancer Aid. The questionnaires were sent to the head of department of the CCCsʼ specialized palliative care teams. Data were collected for the year 2016. Quantitative data were analysed to establish frequencies, given as mean and median. A qualitative section asked for trigger factors, i.e., patient characteristics triggering a palliative care consultation. Evaluation was inductively carried out by content analysis according to Mayring. Results: Data from 15 of the 16 CCCs (94%) were obtained between July and August 2017. In 2016, the median of intensive care patients with palliative care consultations was 33 (minimum 0, maximum 100). The median of nine patients were transferred from an intensive care unit to a palliative care unit (minimum 1, maximum 30). Multidisciplinary ward rounds by both intensive and palliative care staff were available in two CCCs on a regular basis. Two CCCs implemented screening tools to integrate specialized palliative care into intensive care. From 23 responses concerning triggers, three categories were established, i.e., “team’s decision and attitude”, “patient’s condition” and “desires of patients and relatives”. Conclusions: Palliative care is available in German CCCs. However, the degree of integration of specialized palliative care into intensive care units is low. Screening tools are available to identify patients with complex needs and to trigger a palliative care consultation. These tools, as well as joint ward rounds of intensive and palliative care staff, can improve the quality of patient centred care.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Intensive care patient; Interdisciplinary collaboration; Palliative care consultation service; Therapeutic goal setting; Trigger factors